The Laplace transform - Bellman, Richard, 1920-1984 (Series in modern applied mathematics, 1984)
The classical theory of the Laplace Transform can open many new avenues when viewed from a modern, semi-classical point of view. In this book, the author re-examines the Laplace Transform and presents a study of many of the applications to differential equations, differential-difference equations and the renewal equation.